Pengaruh Sarana Pembelajaran Terhadap Kinerja Guru - Ilmi Sawianti; Musdalifah Musdalifah; Susdiyanto Susdiyanto (Manajemen Pendidikan, 2019)
This research discusses the influence of the learning facilities on the teacher’sperformance at Public Junior High School 1 Ulaweng, Bone Regency. It aims to: 1)Describe the actual learning facilities; 2) Describe the actual teacher’s performance;3) examine the influence of learning facilities on teacher’s performance at Public JuniorHigh School 1 Ulaweng, Bone Regency. This research uses quantitative methodologywith ex post facto. the samples of this research are 29 teachers of Public Junior HighSchool 1 Ulaweng, Bone Regency. The data were collected using questionnaires andvisual documentations, and then were analysed using product moment correlationcoefficient, simple linear regression, as well correlation. The data analysis indicatesthat: 1) the actual learning facilities are placed in “adequate” category, indicated by76% ; 2) the favourable score of the actual teacher’s performance with 70% score;3) a 19% positive influence with coefficient correaltion value of 0,437 and regressionequation value of Y: 61.638 + 0.152 X can be seen from the impact of learning facilitieson teacher’s performance.